Biblical narrative and the death of the rhapsode - Kawashima, Robert S., 1966- (Indiana studies in biblical literature., 2004)
Informed by literary theory and Homeric scholarship as well as biblical studies, Biblical Narrative and the Death of the Rhapsode sheds new light on the Hebrew Bible and, more generally, on the possibilities of narrative form. Robert S. Kawashima compares the narratives of the Hebrew Bible with Homeric and Ugaritic epic in order to account for the "novelty" of biblical prose narrative. Long before Herodotus or Homer, Israelite writers practiced an innovative narrative art, which anticipated the modern nov.